2011
DOI: 10.1111/j.1399-6576.2011.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Low central venous oxygen saturation in haemodynamically stabilized trauma patients is associated with poor outcome

Abstract: These data suggest that low ScvO(2) in haemodynamically stabilized patients is associated with a poor outcome and that ScvO(2) represents a potential endpoint of resuscitation in trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Other authors have found similar results [10, 11, 2025]. Hoshking et al showed that levels of 66.5% or lower of ScvO 2 are associated with a worst outcome despite a stable hemodynamic state [15]. Pearse et al described the changes in ScvO 2 after mayor surgery finding an independent association between levels of ScvO 2 (with a cut point of 65%) and the development of POP complications [11].…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Other authors have found similar results [10, 11, 2025]. Hoshking et al showed that levels of 66.5% or lower of ScvO 2 are associated with a worst outcome despite a stable hemodynamic state [15]. Pearse et al described the changes in ScvO 2 after mayor surgery finding an independent association between levels of ScvO 2 (with a cut point of 65%) and the development of POP complications [11].…”
Section: Discussionmentioning
confidence: 72%
“…Based on the results from this study, ScvO 2 monitoring during surgery could be a potential and easily available hypoperfusion marker. It is important to mention that values of ScvO 2 may reflect a low oxygen extraction rate secondary to mitochondrial impairment indicating poor outcomes and limits low levels of ScvO 2 sensibility [15, 33, 34]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations